Effect of some economic indicators on external debt in Sudan from 2002-2017 - Baba, Qosay Mahgoub mohammedsalih; Almahal, Abdulazim Suliman (Journal of Economic, Administrative and Legal Sciences, 2019)
aim to determine the type and tracks of the correlation between variables of deficit of government budget، current account deficit of the balance of payments، exchange rate، Gross Domestic Product(GDP) on the total external debt and clarify the impact of separation or independence of South Sudan in September 2011،also the financial crisis in 2008 on variables of paper، the hypotheses included a positive correlation & impact between the independents variables deficit variables in the general budget and the deficit in the current account of balance of payments، GDP on dependent variable external debt of Sudan as the inverse correlation & impact between the exchange rate with total external debt for the period 2006-2017،used historical approach to describe reasons and evolution of the external debt problem of Sudan causes، in addition، analytical descriptive method by correlation test between the independent variables and the dependent variable to determine the relationship type، also used multiple regression model in measuring and estimating the effect of independent variables on the dependent. The results outcome،the cumulative value of bilateral debt and high interest rates (contractual interest and delayed interest) significantly affect the accumulation of Sudan’s total foreign debt،،maintain both the deficits in budget and in current account also GDP values a positive correlation of statistical significance and a degree of impact on Sudan’s external debt، with Reverse correlation exchange rate، caused from Both of the world financial crisis and the independence of South Sudan in 2011 the، indirect impact on the external debt through its effect of increasing the value of the dollar with a decline of local currency and increasing the budget deficit and its impact on external debt، However، refers the weakness of impact in current account due to growth of gold exports in the period under study. Also the high ratio of bilateral debt owed to non-members of the Paris Club and its high interest rates it is complicated possibility of a solution through the HIPC and others initiatives، The necessary of structural reforms in economic policies by focusing on supporting national production elements as to overcome the obstacles of domestic investment and the abolition of taxes and customs on Alumni projects، microfinance projects، exporters projects as well as trying to follow a rational economic policy using foreign loans in the narrowest limits، and focus on loans on concessional terms،necessary to create an economic partnership between Sudan and creditors countries focus of largest proportion of debts، which is the official bilateral debt (non-members of the Paris Club)، to promote and facilitate the position of Sudan in negotiation of initiative of the HIPC or With regard of interest rate because it is largest and most significant obstruction in Sudan external debt.